Physics Behind the Climate Change - Regmi, Jeevan (Himalayan Physics, 2015)
There is an urgent need for science to inform society about the cost of failure to address the global warming. The challenges offered by global climate change have not been fully recognized by the public and decision making bodies. The severity of climate change has not been taken seriously. It is limited to declarations and propagandas only. Time has come to act globally. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 98-101